The Effects of 6-Month Multi-Component Exercise Intervention on Body Composition in Aged Women: A Single-Arm Experimental with Follow-Up Study - Filipe Rodrigues; José Eduardo Teixeira; António Miguel Monteiro; Pedro Forte (Applied Sciences, 2023)
Multicomponent exercise programs, which combine multiple modalities such as aerobic exercises, strength training exercises, flexibility exercises, and balance exercises, can help to promote healthy aging and prevent chronic diseases in aged women. Thus, the goal of this study is to examine if a multicomponent exercise program could improve body composition in community-dwelling aged women. A 6-month single-arm quasi-experimental research was conducted using a multicomponent exercise program for older adults. The sample included 38 women with a mean age of 63.50 years (SD = 6.47 years). Body composition and anthropometric measurement was conducted from baseline (T1), after intervention (T2), and follow-Up (T3). In addition, after exercise intervention, a significant difference with moderate to large effects was reported for fat mass [η2p = 0.374, p < 0.001)], bone density [η2p = 0.374, p < 0.05)], percentage of water [η2p = 0.374, p < 0.001)], and a metabolic equivalent task [η2p = 0.374, p < 0.05]. Additionally, a significant large effect size between T1 and T2 was verified. However, body composition indicators seem to decrease below baseline levels after concluding exercise intervention (T3). Muscle mass decreased significantly after exercise intervention and mean scores were lower compared to baseline data (T1). Thus, a positive effect of the multicomponent exercise program on body composition was established in this group of community-dwelling aged women. However, the relative improvement in body fat and muscle mass were lost after the exercise program’s conclusion for values below the baselines. Avoiding detraining periods is, therefore, fundamental to maintaining the normal relative body composition.